PENINGKATAN HASIL BELAJAR GEOGRAFI SISWA KELAS XII MATERI PERWILAYAHAN DENGAN MENERAPKAN MODEL GROUP INVESTIGATION - AFIFAH AFIFAH (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This study aims to improve the geography learning outcomes of class XII students on zoning material by applying the Group Investigation (GI) model. The research was conducted at SMA Negeri 64 Jakarta in the odd semester of 2021. The subjects of the research were students of class XII MIPA 1 SMA Negeri 64 Jakarta in the academic year 2021-2022 which consisted of 36 students. Data collection techniques using multiple choice tests with a total of 20 questions, there was an increase in student learning outcomes in each action, starting from the pre-cycle, cycle I and cycle II. The average value of students in the pre-cycle is 75.6 with the number of students who get a complete score of 2 people and an incomplete score of 15 people. After the implementation of the Group Investigation learning model in the first cycle, there was an increase in grades with an average class score of 80.7 with 28 students getting complete marks and 8 incomplete scores. when compared, between pre-cycle and cycle I there was an increase in grades, but students who got a complete score were still less than 80% as the classical KKM, so the researchers continued the research with cycle II. After the second cycle was carried out, the average score of 87.1 students showed an increase, and the number of students who got a complete score was 34 students, but there were still 2 students who had not completed, meaning that students did not complete less than 20%. The conclusion from the results of this study is that the application of the Group Investigation (GI) model can improve student learning outcomes of geography for class XII MIPA I at SMA Negeri 64 Jakarta in the 2021-2022 academic year in odd semesters. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar geografi siswa kelas XII materi perwilayahan dengan menerapkan model Group Investigation (GI). Penelitian dilakukan di SMA Negeri 64 Jakarta pada semester gasal tahun 2021. Subjek penelitian adalah siswa kelas XII MIPA 1 SMA Negeri 64 Jakarta tahun pelajaran 2021-2022 yang terdiri dari 36 siswa. Teknik pengumpulan data dengan menggunakan tes pilihan ganda dengan jumlah soal sebanyak 20 soal, Terjadi peningkatan hasil belajar siswa pada setiap tindakan, mulai dari pra siklus, siklus I dan siklus II. Rata-rata nilai siswa pada pra siklus sebesar 75,6 dengan jumlah siswa yang mendapatkan nilai tuntas sebanyak 2 orang dan nilai tidak tuntas sebanyak 15 orang. Setelah diterapkan model pembelajaran Group Investigation pada siklus I, ada peningkatan nilai dengan rata-rata nilai kelas sebesar 80,7 dengan jumlah siswa yang mendapat nilai tuntas sebanyak 28 siswa dan nilai belum tuntas sebanyak 8 orang. apabila dibandingkan, antara pra siklus dan siklus I ada peningkatan nilai, tetapi siswa yang mendapat nilai tuntas masih kurang dari 80% sebagaimana KKM klasikalnya, sehingga peneliti melanjutkan penelitian dengan siklus II. Setelah dilaksanakan siklus II, nilai rata-rata siswa 87,1 terlihat adanya peningkatan, dan jumlah siswa yang mendapatkan nilai tuntas sebanyak 34 siswa, tetapi masih ada 2 siswa yang belum tuntas artinya siswa tidak tuntas kurang dari 20%. Kesimpulan dari hasil penelitian ini adalah penerapan model Group Investigation (GI) dapat meningkatkan hasil belajar geografi siswa materi Perwilayahan kelas XII MIPA I SMA Negeri 64 Jakarta tahun pelajaran 2021-2022 pada semester gasal.